2006
DOI: 10.1016/j.crhy.2006.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative studies of turbulent transport in fusion plasmas

Abstract: One powerful way to investigate transport is to study the dynamic plasma response to externally applied small perturbations. This paper describes the experimental techniques and basic theory underlying the perturbative approach. It then reviews the most recent results on electron heat transport and discusses their interpretation based on key concepts from electrostatic turbulence theory. Finally it presents some hints for future extensions of the work. RésuméUne puissante méthode d'investigation du transport d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
77
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 56 publications
4
77
0
Order By: Relevance
“…In experiments, short time perturbations to the plasma are triggered by cooling the edge of the plasma using a burst of influx of heavy impurities triggered by laser ablation. 2 The resulting cold pulse is observed to traverse the plasma with speeds much higher than predicted from transport modeling. Often a reversal in the cold pulse polarity is observed, i.e., a temperature increase at certain plasma radius follows the cold pulse trigger instead of a cooling.…”
Section: Introductionmentioning
confidence: 94%
“…In experiments, short time perturbations to the plasma are triggered by cooling the edge of the plasma using a burst of influx of heavy impurities triggered by laser ablation. 2 The resulting cold pulse is observed to traverse the plasma with speeds much higher than predicted from transport modeling. Often a reversal in the cold pulse polarity is observed, i.e., a temperature increase at certain plasma radius follows the cold pulse trigger instead of a cooling.…”
Section: Introductionmentioning
confidence: 94%
“…exploiting the additional information contained in the dynamic response of the plasma rotation to a time variation of the torque source. Modulation at a suitable frequency has the advantage of optimizing the S/N ratio by averaging over several cycles and has been used successfully to study electron and more recently ion heat transport, and also particle and impurity transport (see [18] for a recent review). Its application to momentum transport studies using Neutral Beam Injection (NBI) modulation is a recent development, with a couple of studies reported in JT-60U [19,20], one experiment reported in JET [21,22,23] and one in DIII-D [24].…”
Section: Introductionmentioning
confidence: 99%
“…These and other non-linear transport properties have been analyzed using perturbations (often via the heat pulse diffusivity χ HP ) at different operating points and comparing them to each other and to steadystate results (power balance diffusivity χ P B ) [34,2]. Alternatively, model codes based on the physics are used to fit parameters of the non-linear models, e.g., [20,35]. The problem with such an approach is that they generally prove the existence of a non-linearity, but their interpretations depend on the used transport model.…”
Section: Introductionmentioning
confidence: 99%
“…This list is far from exhaustive and for a more complete overview of such experiments and its history the reader is referred to [2,3,20].…”
Section: Introductionmentioning
confidence: 99%